Image and Text - Jason DeHart (University of Oklahoma Libraries, 2021)
Jones and Woglom (2014) pointed to the tensions that sometimes exist around using comics and graphic novels as literary work in the classroom. It is from this noted tension that we arrive at a call for both critical and empirical studies that examine this issue more closely. If, indeed, graphic novels have potential for instruction, then in what ways are teachers using them across educational settings? Beyond popularity, how do children and adolescents respond to these works? How do educators align themselves with the counter-narrative of comics as texts worthy of analysis and exploration, and how do they send this message to critics of the medium? In what ways do graphic novels sit within the context of antiracist and social justice-oriented pedagogy? Download PDF for full description and submission requirements. Submissions due DECEMBER 15, 2021.